The role of 18F-FDG-PET/ceCT in peritoneal mesothelioma. Issue 4 (April 2017) - Dubreuil, Julien; Giammarile, Francesco; Rousset, Pascal; Rubello, Domenico; Bakrin, Naoual; Passot, Guillaume; Isaac, Sylvie; Glehen, Olivier; Skanjeti, Andrea
Abstract : Purpose: The aim of this study was to assess glucose metabolism of multicystic peritoneal mesothelioma and epithelioid peritoneal mesothelioma by fluorine-18 fluorodeoxyglucose ( 18 F-FDG)-PET/contrast-enhanced computed tomography (ceCT) and to assess its prognostic impact. Materials and methods: Twenty-three (14 women) patients, without previous treatment, underwent 18 F-FDG-PET/ceCT before peritoneal mesothelioma cytoreductive surgery and intraperitoneal chemotherapy. 18 F-FDG-PET/ceCT was interpreted prospectively as positive or negative. Maximum standardized uptake value (SUVmax ) of each lesion was measured retrospectively on the basis of postsurgery data. At laparotomy, disease extension was estimated with the Peritoneal Cancer Index. The median follow-up was 27 months (95% confidence interval: 12.9–37.8); progression-free survival (PFS) was recorded. Results: Nine patients were affected by multicystic and 14 were affected by epithelioid peritoneal mesothelioma. PET showed mild focal uptake in one case of multicystic peritoneal mesothelioma, whereas in eight patients, no abnormal uptake was observed. PET was positive in 12/14 patients with epithelioid peritoneal mesothelioma. Sensitivity, specificity and accuracy were respectively 86, 89 and 87%; the qualitative assessment was statistically different ( P =0.0020, χ 2 ). Multicystic peritoneal mesothelioma histology was significantly associated with lower SUVmaxlesion ( P =0.0061), SUVmaxlesion/liver ( P =0.0025), Peritoneal Cancer Index, younger age, and it was observed only in women. Recurrence was observed on nine patients affected by epithelioid peritoneal mesothelioma, whereas no recurrences were observed among multicystic peritoneal mesothelioma patients. SUVmaxlesion ( P =0.0278) and age ( P =0.0241) were significantly associated with PFS in patients with epithelioid peritoneal mesothelioma. Conclusion: 18 F-FDG-PET/ceCT showed significant differences between multicystic and epithelioid peritoneal mesothelioma, whereas SUVmaxlesion was associated with PFS in the latter. Although multicentre prospective studies are necessary, 18 F-FDG-PET/ceCT appears to be a promising tool in patients affected by peritoneal mesothelioma.